Implementation of Stock Epinephrine in Chartered Versus Unchartered Public‐School Districts. (13th March 2022) - Neupert, Kathryn B.; Huntwork, Margaret P.; Udemgba, Chioma; Carlson, John C.
ABSTRACT: BACKGROUND: Access to unassigned epinephrine is critical for schools to treat anaphylaxis. Low socioeconomic status is associated with decreased access to epinephrine in the school setting. In and around New Orleans, physicians partner with schools to assist with stocking unassigned epinephrine autoinjectors (EAIs). New Orleans' decentralized public charter school district makes widespread adoption challenging. METHODS: Physicians partnered with New Orleans decentralized public charter schools, as well as neighboring centralized public school districts, to perform training on recognizing and treating anaphylaxis, assist with the adoption of school policy for stock epinephrine, and aid with obtaining stock EIAs free‐of‐cost through the EpiPen4Schools® program. We used publicly available school enrollment data and our own calendar records to calculate how many children we covered with stock epinephrine per hour of physician or administrator time. RESULTS: For centralized school districts, we cover approximately 4000 children with stock epinephrine per hour of time. For the decentralized district of New Orleans, we estimate covering only 400 children with stock epinephrine per hour of time. CONCLUSION: Decentralized school districts reduce educational disparities, but require more time and energy to get EAIs in place than centralized school districts do.